THE TECHNICAL AND ECONOMICAL PERFORMANCE OF THE “ABC” TYPE PADDY DRYER - Sutrisno Sutrisno; M. Wahyudin; E. Eko Ananto (Indonesian Agency for Agricultural Research and Development, 2001)
Farmers in the villages always face the same problem of how to reduce the moisture content of paddy harvest during harvest and postharvest time, especially in wet season. At the farm level, the grain quality is poor and alternative drying using kerosene fuel is very costly. The objective of this research was to design and evaluate the technical and economical performance of drying paddy using an equipment known as